Comparison of Clinical, Hematological and Bacteriological Profile of Neonatal Sepsis between Term and Preterm Babies - Hasina Mamtaz, Syeda Shahnoor; Karim Chowdhury, Abu Hena Md Saiful (Journal of Chittagong Medical College Teachers' Association, 2021)
Background: Neonatal sepsis is an important public health problem with a high morbidity and mortality. Globally, it has been reported that preterm newborns have a 13 times greater risk of death than full term newborn babies. Clinical, hematological parameters and the spectrum of organisms causing neonatal sepsis may vary between term and preterm. Present study is a good opportunity to evaluate clinical, haematological & bacteriological profile of neonatal sepsis in preterm & term. Materials and methods: This hospital based observational and comparative study was carried out in Special Care Newborn Unit (SCANU) of Chittagong Medical College Hospital where a total of 100 clinically suspected neonatal sepsis cases was enrolled, out of which 50 were preterm and 50 term neonates. Clinical, hematological and bacteriological profiles were compared between two groups. Results: Hypothermia was an important clinical feature occurring in 70.0% preterm and 16.0% term cases. Mean platelet count was 1.04±0.73 lacs/cmm in preterm and 1.52±0.78 lacs/cmm in term cases. In term and preterm neonates CRP were observed to be 39.42±32.99mg/L and 26.20±22.25 mg/L (p=0.021). Klebsiella species was the predominant isolated bacteria in both groups, showing 16.0% in preterm and 14.0% in term cases, followed by S. aureus, Acinetobacter species and Candida species. Conclusion: Neonatal sepsis is an important cause of morbidity and mortality. There is need of large scale studies, in hope of developing a better prevention policy in both term and preterm babies. JCMCTA 2021 ; 32 (1) : 21-25